SLC38A5 aggravates DC-mediated psoriasiform skin inflammation via potentiating lysosomal acidification - Leqing Zhu; Xichun Xia; Guangqiang Li; Chuyun Zhu; Qingqing Li; Baocheng Wang; Nan-Xi Shi; Zhiwei Lei; Shuxian Yang; Zhanpeng Zhang; Haishan Li; Jingyi Tan; et al. (Cell Reports, 2023)
Summary: Amino acid (aa) metabolism is closely correlated with the pathogenesis of psoriasis; however, details on aa transportation during this process are barely known. Here, we find that SLC38A5, a sodium-dependent neutral aa transporter that counter-transports protons, is markedly upregulated in the psoriatic skin of both human patients and mouse models. SLC38A5 deficiency significantly ameliorates the pathogenesis of psoriasis, indicating a pathogenic role of SLC38A5. Surprisingly, SLC38A5 is almost exclusively expressed in dendritic cells (DCs) when analyzing the psoriatic lesion and mainly locates on the lysosome. Mechanistically, SLC38A5 potentiates lysosomal acidification, which dictates the cleavage and activation of TLR7 with ensuing production of pro-inflammatory cytokines such as interleukin-23 (IL-23) and IL-1β from DCs and eventually aggravates psoriatic inflammation. In summary, this work uncovers an auxiliary mechanism in driving lysosomal acidification, provides inspiring insights for DC biology and psoriasis etiology, and reveals SLC38A5 as a promising therapeutic target for treating psoriasis.